Effects of Drought on Mortality in Macro Urban Areas of Brazil Between 2000 and 2019. (8th March 2022) - Salvador, C.; Vicedo‐Cabrera, A. M.; Libonati, R.; Russo, A.; Garcia, B. N.; Belem, L. B. C.; Gimeno, L.; Nieto, R.
Abstract: A significant fraction of Brazil's population has been exposed to drought in recent years, a situation that is expected to worsen in frequency and intensity due to climate change. This constitutes a current key environmental health concern, especially in densely urban areas such as several big cities and suburbs. For the first time, a comprehensive assessment of the short‐term drought effects on weekly non‐external, circulatory, and respiratory mortality was conducted in 13 major Brazilian macro‐urban areas across 2000–2019. We applied quasi‐Poisson regression models adjusted by temperature to explore the association between drought (defined by the Standardized Precipitation‐Evapotranspiration Index) and the different mortality causes by location, sex, and age groups. We next conducted multivariate meta‐analytical models separated by cause and population groups to pool individual estimates. Impact measures were expressed as the attributable fractions among the exposed population, from the relative risks (RRs). Overall, a positive association between drought exposure and mortality was evidenced in the total population, with RRs varying from 1.003 [95% CI: 0.999–1.007] to 1.010 [0.996–1.025] for non‐external mortality related to moderate and extreme drought conditions, from 1.002 [0.997–1.007] to 1.008 [0.991–1.026] for circulatory mortality, and from 1.004 [0.995–1.013] to 1.013 [0.983–1.044] for respiratory mortality. Females, children, and the elderly population were the most affected groups, for whom a robust positive association was found. The study also revealed high heterogeneity between locations. We suggest that policies and action plans should pay special attention to vulnerable populations to promote efficient measures to reduce vulnerability and risks associated with droughts. Plain Language Summary: Drought is a complex phenomenon that affects environmental and socioeconomic sectors, with important implications in public health. This phenomenon may impact different groups among the population unequally, but thus far, very few studies have explored the potential differences in drought effects on mortality in different population groups separated by sex and age. Thereby, further, and conclusive studies are required to get a deeper understanding of the populations at potential risk, especially considering the expected increase in frequency and intensity of drought events in several regions of the world such as Brazil due to climate change, posing a growing threat to health. In this study, we aimed to analyze for the first time the short‐term effects of different levels of drought severity on weekly no‐external, circulatory, and respiratory mortality in 13 major macro‐urban areas of Brazil across 2000–2019 in the total population, incorporating an assessment by sex and six age groups to know ultimately the structure of the population at risk. We found that overall, accounting for the 13 Brazilian urban areas, there were strong gender differences, with females being the most affected. Moreover, drought mostly influenced mortality in children and the elderly. We also found heterogeneity across urban locations. Key Points: Drought influenced positively non‐external, circulatory, and respiratory mortality in Brazilian urban areas in specific population groups Females, children, and the elderly were the populations more at risk Drought mostly affected mortality in those locations that suffered higher number and severity of drought conditions